2005
DOI: 10.1007/s11101-005-2606-6
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene Saponins from Polygalaceae

Abstract: The aim of this review is to give updated results on the chemistry and biological activities of Polygalaceae saponins from literature data and from authors' studies. During the last decade the improvement of isolation and structure elucidation techniques allowed the characterization of about 150 complex triterpene saponins from Polygalaceae having mainly preatroxigenin, medicagenic acid and presenegenin as aglycone. The sequence 3-O-(b-D-glucopyranosyl)-presenegenin 28-[O-a-L-rhamnopyranosyl-(1 fi 2)-b-D-fucop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…However, reports have shown that polygalasaponins could be toxic to animals, leading to nose bleeding, gastrointestinal tract abnormality, and even death (Xue et al, 2009;Lin et al, 2012), which seriously limits their application and development. Recently, researchers have found that the hydrolysate of polygalasaponin (HPS) could attenuate or abrogate the toxicity (Lacaille-Dubois and Mitaine-Offer, 2005). This makes HPS a better choice in dementia treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, reports have shown that polygalasaponins could be toxic to animals, leading to nose bleeding, gastrointestinal tract abnormality, and even death (Xue et al, 2009;Lin et al, 2012), which seriously limits their application and development. Recently, researchers have found that the hydrolysate of polygalasaponin (HPS) could attenuate or abrogate the toxicity (Lacaille-Dubois and Mitaine-Offer, 2005). This makes HPS a better choice in dementia treatment.…”
Section: Introductionmentioning
confidence: 99%
“…They were reported to significantly affect cancer cell growth and have therefore incited considerable interest of many researchers. Recent reviews have been published focusing on isolation, structure elucidation, biological activities of triterpenoids (Mahato and Sen 1997;Tan et al 1999;Connolly and Hill 2000;Sparg et al 2004;Lacaille-Dubois and Mitaine-Offer 2005;Park et al 2005;Piacente et al 2005;Lanzotti 2005), biosynthesis (Henry 2005;Szakiel et al 2005), classification, and occurrence of saponins (Vincken et al 2007), but no exclusive research work is done on AATS and informations on these molecules are dispersed in the available literature.…”
Section: Introductionmentioning
confidence: 99%
“…Triterpene glycosides are good candidates for this purpose due to their aglycon bearing various glycosidic moieties, from a single sugar to an oligosaccharide chain, as mono or bidesmosidic structures. Many of these compounds have been isolated and characterized during the last decades [15,16]. Herein we report the selection of isolated natural triterpene glycosides as structures bearing different glycosyl moieties and their immunochemical characterization in MS patientsʼ sera.…”
mentioning
confidence: 99%